Ulama Kedah And Tabagsel Network In 1900-1950 - Sehat Sultoni Dalimunthe; Zainal Efendi Hasibuan; Ali Amran (IAIN Padangsidimpuan, 2020)
The Kedah and Tabagsel Ulama Network in 1900-1950 was important to be discussed considering that there were some scholars from Tabagsel who were studying in Kedah. After that, they proceed to Mecca. After they returned to Indonesia they established a pesantren. Among them, Sheikh Ahmad Daud (1891-1981), Muhammad Mukhtar Harahap, founder of the Padang Padang Lawas al-Mukhtariyah boarding school, Sheikh Abdul Qadir Mandily, and Sheikh Juneid Thola from Kotanopan. For education experts in Malaysia mention that since 1924-1945 there was a golden age of Islamic education in Kedah. Many Ulama in Kedah came from Patani because of security factors that were not conducive, so they migrated to Kedah. Later, after the Tabagsel ulemas came back and established Islamic boarding schools in their respective regions, they gave colors to Islamic education for the community